The logic of reliable inquiry - Kelly, Kevin T. (Logic and computation in philosophy., 1996)
This illustrated work searches for the answers to such questions as whether standard methodological recommendations help or hinder the reliability of inquiry. It uses techniques and concepts drawn from formal learning theory, topology and the theory of computability.